ABAKA (Musa textilis Nee) SEBAGAI SUMBER SERAT ALAM, PENGHASIL BAHAN BAKU PULP / Abaca (Musa textilis Nee) As Thesourceof Naturalfiber, Producingraw Materialfor - Budi Santoso; Mastur Mastur; Fitriningdyah Tri Kadarwati (Puslitbang Perkebunan, 2016)
Abaca-producing natural fiber as raw material for pulp paper money. Natural fibers derived from abaca, have environmentally friendly nature and local wisdom, highly favored by consumers manufacturer. Nowadays the need for abaca fiber in the country is still imported. Pulp and paper are derived from abaca has advantages including a tear-resistant, when it becomes difficult falsified paper or paper produced is used for Paper that is difficult to imitate, stamp paper dukomen (seals, certificates, diplomas and other important papers). Bank Indonesia (BI) in 2014 is more serious to use raw materials of cotton fiber and abaca fiber in the country. This is in accordance with the Currency Act N0. 7 Year 2011 on article 9 (2) in order to give priority to domestic raw materials (local) to maintain the quality, safety and competitive prices in the printing Rupiah. The first harvest abaca at age 18-20 months after planting. At that time there has been no income for farmers, their inter-cropping between chili + abaca provide a source of income, because chili is a seasonal crop that yields chilli can assist in meeting the needs of farmers in financial trouble. Besides, there is no plant stand (Jabon, or sengon). The pattern of intercropping abaca + small chilli may generate profits of Rp. 21.333 million, - thus the development of abaca has good prospects. The purpose of the writing of this review is to provide support for the existence of abaca development innovation as a source of natural fiber which contribute in providing raw materials of paper money dicanakan by Bank Indonesia and to create employment in rural areas, and provide a source of income of farmers.